NURSES’ KNOWLEDGE OF EARLY WARNING SCORE AT A PRIVATE HOSPITAL IN EASTERN INDONESIA - Janwar Olang; Marisa Junianti Manik; Oberlin Simamora (Universitas Pelita Harapan, 2019)
Early Warning Score (EWS) is an approach to identify clinical decline and early detection of abnormal condition in regard with patients at hospital. This early clinical decision could influence on patient morlality rates and quality of nursing care. The purpose of this research was to describe nurses’ knowledge about EWS at a private hospital in Eastern part of Indonesia. This research applied a quantitative descriptive method. Total of 48 nurses at a private hospital in Eastern part of Indonesia were recruited in this study. This study used a descriptive analysis. This study revealed that most nurses (81.25%) were at the level of adequate in regard with their knowledge of EWS. Further study is recommended to explore nurses compliance on EWS implementation in hospital and how it is associated with patients’ deterioration conditions.